Reinforcing Teachers’ Content Knowledge Competence of Civics Education through Implementing the Actual Civic Issues Strategy - Putra, Hanry Pratama; Muchtarom,; Triyanto,; Winarno, (International Journal of Psychosocial Rehabilitation, 2020)
The information development in the 21st century has an impact on the fast spread of citizenship issues. The raising problem at the field was the lack of Civic content knowledge competence of the teachers as the learning providers in delivering and managing actual Civic issues that are in accordance with the students' competence needs in the 21st century. Consequently, the learning materials majorly have turned into static and underdeveloped, and even the phenomenon of interpreting issues is arbitrary and left without critical contemplation. This research aims at determining the reinforcing strategy of teachers' content knowledge competence of Civics Education through the choice of actual citizenship issues. The research was conducted on teachers of Civics Education subject at Junior High Schools in the city of Surakarta; this was designed with qualitative research methods. The data collection was carried out through document study, interview, and observation. The data analysis techniques applied data reduction, data presentation, drawing conclusions and verification. This research indicated that reinforcing the teachers' knowledge competence of Civics Education content can be realized through the choice of actual Civic issues as conceptualized into the 4CS skills (Creativity, Critical thinking, Communication, Collaboration) in accordance with the students’ competence needs in the 21st century. The actual citizenship enables teachers strengthening their knowledge competence of Civics Education Content.